Factors Facilitating the Uptake of Post-Abortion Care Services in Dar es Salaam, Tanzania (Tanzania Journal for Population studies and Development, 2021)
Unsafe abortion is associated with health complications which contribute to the global burden of maternal mortality. Post-abortion care is then promoted as a key strategy for addressing complications associated with unsafe, induced and spontaneous abortion. Prompt utilization of post abortion care (PAC) services has high chances of reducing the morbidity and mortality associated with abortion complications. This article employs data from a cross-sectional study in Temeke District in Dar es Salaam, Tanzania, involving 103 women who sought PAC services from health facilities. Qualitative and quantitative approaches were applied in the collection and analysis of data. Random sampling was used to select the facilities, while the respondents were recruited through criterion sampling. A semi-structured questionnaire was administered to women who utilized PAC services when they were about to exit health facilities. A descriptive thematic analysis approach was employed to analyse qualitative information, while descriptive statistics and univariate approaches were used to analyse quantitative data. The findings revealed that the availability of PAC services in the study facilities, sharing of information about one’s health status, ability to cater for transport and treatment costs, privacy and less waiting time, as well as availability and reliability of transport for emergency cases were the main factors that facilitated the uptake of PAC services. Also, the findings suggest that in areas where abortion is stigmatized and legally restricted, utilization of PAC services can be enhanced if such services are openly available and affordable. Moreover, privacy and less waiting time may further guarantee the uptake of PAC services. Likewise, there is a need to raise awareness about PAC and the availability of PAC services in Tanzania. Also, efforts should be made to ensure that privacy is maintained throughout the delivery of care to enhance the utilization of PAC services.